Sick of Being Unemployed? Interactions Between Unemployment and Sickness Insurance in Sweden - Laura Larsson (Uppsala University, Department of Economics, 2002)
This paper examines the incentive effects caused by the interactions between unemployment insurance (UI) and sickness insurance (SI), two important components of Sweden's social insurance system. There are two main topics of interest: how the sickness report rate and the length of the subsequent sick period among the unemployed are affected by (i) the limit of 300 workdays for UI benefits, and (ii) the difference in maximum compensation between UI and SI benefits. Results obtained by duration analysis suggest that sick reports increase as the UI benefit expiration date approaches. There is also evidence of an incentive effect on the sick-report rate because SI offers greater compensation than UI. But neither of these factors seems to have a significant effect on the length of the sick period.
urn:nbn:se:uu:diva-2225
Keywords: C41; H55; I18; J64; J65; 330; Unemployment insurance; sickness insurance; health; duration analysis; discrete hazard models; Arbeitslosigkeit; Krankheit; Krankenversicherung; Arbeitslosenversicherung; Schweden